2019
DOI: 10.1364/oe.27.006719
|View full text |Cite
|
Sign up to set email alerts
|

Regularized pseudo-phase imaging for inspecting and sensing nanoscale features

Abstract: Recovering tiny nanoscale features using a general optical imaging system is challenging because of poor signal to noise ratio. Rayleigh scattering implies that the detectable signal of an object of size d illuminated by light of wavelength λ is proportional to d 6 /λ 4 , which may be several orders of magnitude weaker than that of additive and multiplicative perturbations in the background. In this article, we solve this fundamental issue by introducing the regularized pseudo-phase, an observation quantity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…A line-scanning laser has been applied to improve detection speed [9,10]. Both the intensity and phase information of scattered light can be utilized with good robustness [11][12][13]. Localized physical phenomena of evanescent waves or Raman scattering allow the detection of sub-micron defects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A line-scanning laser has been applied to improve detection speed [9,10]. Both the intensity and phase information of scattered light can be utilized with good robustness [11][12][13]. Localized physical phenomena of evanescent waves or Raman scattering allow the detection of sub-micron defects [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…49 In a macroscale imaging system, a high-NA objective lens enables optical trapping and sensing of nanoscale objects. 50,51 Analogously, the microlens effect of cells make it possible to use a single cell to trap, image, and sense nanoparticles as was successfully demonstrated very recently. 52 A signicant difference to conventional optical imaging is that the single cell can be operated in contact mode such that the possible evanescence-propagation coupling can facilitate super-resolution imaging.…”
Section: Pnj Generators In the Naturementioning
confidence: 99%
“…However, the imaging resolution beyond the Rayleigh limit via the contacted "microsphere lens," makes the PNJ-assisted imaging signicantly different to any known conventional far-eld-based imaging modalities. 51,167,168 Specically, it has been reported that a solid immersed lens (nanolens) with n ¼ 1.5 can resolve features beyond the diffraction limit. 169 These nanolenses, in contrast to geometrical optics lenses, exhibit curvilinear trajectories of light, resulting in remarkably short near-eld focal lengths.…”
Section: Deep-subwavelength Fwhm and Neareld Effect Of Pnjsmentioning
confidence: 99%
“…Finally, taking into account the growing amount of data, techniques such as CFS lack the tools of being able to process raw data sets automatically and effectively. Recently, to overcome the challenges of detection and classification of smaller particles, machine learning methods, including the regularized matrix-based imaging framework [19], principal component analysis [20], and convolutional neural networks [21] were applied to image-based defect detection.…”
Section: Introductionmentioning
confidence: 99%